PERAN PENYULUH PERTANIAN DALAM PENGENDALIAN HAMA PADA TANAMAN SAYURAN DI DESA LAWONUA KECAMATAN BESULUTU KABUPATEN KONAWE - Jumria Arifin; Hartina Batoa; Salahuddin Salahuddin (Universitas Halu Oleo, 2023)
The purpose of this research is to determine the role of agricultural extension workers in pest control in vegetable crops in Lawonua Village, Besulutu District, Konawe Regency. The research location was chosen on purpose (intentionally) with the knowledge that some residents of Lawonua Village, Besulutu District, Konawe Regency work as vegetable farmers. The research was conducted in August-September 2022 with a total of 11 informants consisting of 10 vegetable farmers and 1 extension worker. This study uses qualitative analysis. The results showed that the role of agricultural extension agents in controlling pests in vegetable crops had a good role as seen from the role of extension workers as facilitators, motivators and educators in helping to improve vegetable farming.